2008
DOI: 10.4103/0019-5154.44789
|View full text |Cite
|
Sign up to set email alerts
|

A cross section of skin diseases in rural Allahabad

Abstract: Background:The pattern of skin diseases varies form one country to another and across different parts within the same country. A two-day multispecialty medical camp was held among the local population at the district of Kausambi, Allahabad, UP, in October 2005. A cross section of pattern of skin diseases observed at the camp is reported and compared with similar studies in literature.Materials and Methods:All cases attending the medical camp were included in the study. All those with dermatological complaints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 4 publications
9
51
1
Order By: Relevance
“…[1,[6][7][8][9] Patients in these peripheral stations and difficult to reach terrains usually do not seek any specialized treatment for dermatological diseases, or are provided preliminary treatment by non-specialists. This is because of long distances from the health centres in some cases, but mostly because of non-availability of specialized dermatology services.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…[1,[6][7][8][9] Patients in these peripheral stations and difficult to reach terrains usually do not seek any specialized treatment for dermatological diseases, or are provided preliminary treatment by non-specialists. This is because of long distances from the health centres in some cases, but mostly because of non-availability of specialized dermatology services.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Age groups between 15-29 years (43.78%) were reported to have maximum incidence followed by 30-44 years (24.45%). Age group of 11-30 years was reported to have maximum incidence in a study from Allahabad, 14 while other studies reported maximum incidence in age groups of 20-30 and 30-40 years.…”
mentioning
confidence: 83%
“…8 The prevalence of skin disorders among students was calculated as 44.50% in our study. While in other studies it is found as 76.65%, 53.6%, 69.38%, and 69.0%, by Kuruvilla,9 Vallia, 10 Yaseen, 11 and Suman Saurabh, 5 respectively in school children.…”
Section: Discussionmentioning
confidence: 99%